2021
DOI: 10.15376/biores.16.2.2853-2860
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the western juniper (Juniperus occidentalis) strandboard

Abstract: This work investigated the feasibility of using western juniper (Juniperus occidentalis) as a material to manufacture oriented strandboard (OSB) panels. Four different material combinations of juniper sapwood, heartwood, and fibrous bark were compared with regular southern yellow pine (Pinus sp.) strands. The OSB panels were made at an oven-dry density of 560 kg/m3. One pine control panel was also made at a higher density of 650 kg/m3 with a 5% addition of phenol formaldehyde (PF) resin and a 0.5% addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…and falcata wood (Falcataria moluccana), and the authors concluded that, based on the results, strand boards obtained from rubber and falcata have the potential to be commercialized [6]. In the United States of America, a work investigated the feasibility of using western juniper (Juniperus occidentalis) as a material to manufacture oriented strand board (OSB) panels, and according to the authors, the properties of the juniper panels were found to be equivalent or slightly superior to those of the southern yellow pine panels at the same density level, except for the modulus of elasticity [7]. These studies around the world demonstrate that researchers are interested in exploring new alternative species that can be used in the manufacturing of OSB panels.…”
Section: Introductionmentioning
confidence: 99%
“…and falcata wood (Falcataria moluccana), and the authors concluded that, based on the results, strand boards obtained from rubber and falcata have the potential to be commercialized [6]. In the United States of America, a work investigated the feasibility of using western juniper (Juniperus occidentalis) as a material to manufacture oriented strand board (OSB) panels, and according to the authors, the properties of the juniper panels were found to be equivalent or slightly superior to those of the southern yellow pine panels at the same density level, except for the modulus of elasticity [7]. These studies around the world demonstrate that researchers are interested in exploring new alternative species that can be used in the manufacturing of OSB panels.…”
Section: Introductionmentioning
confidence: 99%